Substitution effects on the magnetic phase transition and magnetocaloric effects in nanolaminated AlFe2B2 alloys - Shiqi Wang; Pu Liu; Jiamin Chen; Weibin Cui (AIP Advances, 2022)
Substitution effects of V, Ti and C in AlFe2−xVxB2 (x ≤ 0.15), AlFe2−yTiyB2 (y ≤ 0.15) and AlFe2B2−zCz (z ≤ 0.2) alloys have been investigated. The main phase of these alloys is crystallized in the orthorhombic Cmmm-type structure. The Curie temperature (Tc) of these compounds can be tuned from 278 K to be around 300 K depending on the substitution amount. No thermal and magnetic hysteresis can be observed, suggesting the magnetic transition of these alloys is the second-order nature. For a field change of 7 T, the maximum of entropy change (−ΔSmax) of 4.0 J Kg−1 K−1, 4.2 J Kg−1 K−1 and 3.9 J Kg−1 K−1 has obtained in AlFe1.9V0.1B2, AlFe1.9Ti0.1B2 and AlFe2B1.9C0.1 alloys. Tunable Tc and wide temperature span in AlFe2B2 phase suggest that AlFe2B2-base alloys have a potential application as a refrigerant in magnetic refrigeration.